PENDAMPINGAN BACA TULIS AL-QUR’AN PADA SISWA SEKOLAH DASAR MELALUI KEGIATAN ROAD TO TPA NAGARI TANJUNG BARULAK - Safrizal, Safrizal; Libraniati, Ringga; Ratna Sari, Bunga; Arafat Lubis, Maulana; Azizan, Nashran (Cendekia Citra Gemilang Scholar Foundation, Indonesia, 2025)
The implementation of the value of reading and writing the Qur'an in elementary school children is an important effort in forming a generation that is moral and knowledgeable. The